Challenges for teaching Administration and Accounting in the context of Emergency Remote Teaching (ERT): overcoming barriers and advancing in learning (Olhar de Professor, 2023)
This study examines the primary challenges encountered by professors in the Business Administration and Accounting courses at educational institutions in the metropolitan region of Belém during the implementation and maintenance of Emergency Remote Teaching (ERT) amid the pandemic. Through interviews, it was found that professors invest more time in class preparation without always receiving satisfactory compensation. They also acknowledge a decline in student learning, influenced by students' socioeconomic status, aligning with existing literature. Furthermore, practical, and calculation-related subjects were identified as the most challenging in the Emergency Remote Teaching (ERT) model. To address remaining gaps, further research is needed to understand the limitations, challenges, and possibilities of the hybrid teaching model, which aims to replace remote teaching.
Keywords: Emergency Remote Teaching (ERT).; COVID-19.; Teacher Training.; High Education.